Pengaruh Structured Growth Reflection Workbook Berbasis Growth Mindset terhadap Self-Regulated Learning Siswa Kelas V Sekolah Dasar - Rahayuning Safitri, Nadiya; Sudiyana, Benecditus; Sadino (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of the Structured Growth Reflection Workbook as a metacognitive scaffolding tool in improving Self-Regulated Learning (SRL) among elementary school students. The main issue underlying this research is the low level of student learning independence, characterized by high dependency on teacher direction, minimal learning targets, and low self-reflection skills. This study employed a mixed methods approach with an embedded experimental design (one-group pretest-posttest). The research sample consisted of fifth-grade students from a State Elementary School in Mojolaban District, Sukoharjo, Central Java, selected through a total sampling technique. The intervention was carried out through the implementation of a growth mindset-based reflective learning routine for four months. Quantitative data analysis utilized a paired sample t-test and Cohen's d to measure effect size, while qualitative data were analyzed thematically. The results showed a significant increase in students' SRL scores () with a large effect size category, namely from a mean of 2.47 to 3.87. The novelty of this research lies in the integration of Zimmerman's SRL syntax and Dweck's growth mindset into a practical daily reflective workbook. The routine use of the workbook proved to facilitate students in internalizing the SRL stages through a systematic process of planning, monitoring, and self-evaluation. This product contributes to the development of a reflective learning model that can be integrated across various subjects in elementary schools to build sustainable learning independence.